Troubadours and trouvères in Russian: Contribution to the problem of translating medieval lyrics - O. V. Smolitskaya (Шаги, 2024)
The article deals with the problem of translating into Russian medieval French and Provencal lyrics of the troubadours and trouvères. The author relies on M.L. Gasparov’s concept of translation; in particular, he speaks about the distinction between “distancing” and approximating, domesticating translation. The article analyzes in detail the translations of a rondeau by Chrétien de Troyes by V. Mikushevich and A. Parin, as well as the translations of a canzona by Jaufre Rudel by V. Dynnik and A. Naiman. The analysis reveals semantic deviations and transformations, as well as techniques that destroy the authentic poetics of courtly lyrics. The author speaks about the inevitability of semantic losses when making a translation into the modern Russian poetic system. When creating a poetic translation, which can be perceived as a “good poem” from the point of view of the translator and his readers, it turns out that exactly what underlies the poetics of the troubadours is unused — traditionality, formularity, a specific ratio of stable tradition and author’s individuality. In order to avoid losses as much as possible, it is proposed to resort to vers libre (free verse). The author refers to the concept of M.L. Gasparov, who wrote about the advantages that free verse offers a translator.